An Analysis of Quality Services on Patient Satisfaction Outside at Putri Bidadari Hospital Stabat Langkat Regency - Ramadhan Efendi; Ermi Girsang; Ali Napiah Nasution; Chrismis Novalinda Ginting (Budapest International Research and Critics University, 2022)
The purpose of the study was to determine the difference in service quality based on patient safety, effectiveness and efficiency, and patient orientation, as well as patient satisfaction between patients using BPJS and the general public. The study was conducted by as many as 60 respondents consisting of 30 BPJS patients and 30 general patients in out patient care for Hospitsl Putri Bidadari Stabat, Langkat Regency. Analysis of the data used is the independent t-test and then analyzed the effect of the independent variables on the dependent using multiple regression analysis. The results showed that there were significant differences in service quality based on patient safety, effectiveness and efficiency, and patient orientation, as well as patient satisfaction among patients using BPJS and the general public, as well as the influence between patient safety, effectiveness and efficiency, and patient-oriented variables on patient satisfaction. From the results of these equations, it is known that the three independent variables, namely patient safety, effectiveness and efficiency, and patient-oriented services have a positive effect on customer satisfaction. This means that if patient safety, effectiveness and efficiency, and patient-oriented services, the higher patient satisfaction.